Nursing team's role in the breastfeeding process in the face of early weaning prevention (Research, Society and Development, 2021)
There has been an increase in exclusive breastfeeding rates in Brazil, however, they are still below that recommended by the World Health Organization. This article aims to investigate the role of nurses in encouraging breastfeeding in the prevention of early weaning. This is a bibliographical research, carried out in Lilacs, Scielo and VHL; We used, as inclusion criteria of the articles, productions performed between 2014 and 2020, without language specification and only articles available in full Were excluded Those that did not talk with the theme of the research. Twenty-three articles and 5 publications from the Ministry of Health were selected. The study brought the benefits of breastfeeding in the mother-baby link, in addition to addressing the importance of good nursing care to avoid the process of early weaning, such as competencies, health education and health promotion were addressed. It is concluded that a nursing care based on health promotion and placing itself as a transmitting agent of knowledge makes this breastfeeding process better accepted by the woman since she is already prepared for the situations that may arise and how to act before them, and as a consequence, it is possible to demystify the various knowledge of common sense.